The complete mitochondrial genome of Anoplistes halodendri (Coleoptera: Cerambycidae) - Bairong Lin; Rong Deng; Jiayi Ma; Xiaoqian Weng; Xiong Guan (Mitochondrial DNA. Part B. Resources, 2020)
In this study, we report the complete mitochondrial genome of Anoplistes halodendri, which covers a total of 15,697 bp in length with 28.27% GC content. The complete mitochondrial genome is composed of 12 protein-coding genes (PCGs) and also contains 22 transfer RNA genes (tRNAs) and two ribosomal RNA genes (rRNAs). Phylogenetic analysis of the A. halodendri with other 21 different species of Cerambycidae indicated that A. halodendri formed an isolated clade and belong to Cerambycinae. The results will be helpful to study the evolutionary relationship among the subfamilies of Cerambycidae.